Structured decision-making shows broad support from diverse stakeholders for habitat conservation and restoration in Kenya’s Central Highlands - Gwili E.M. Gibbon; Martin Dallimer; Hassan Golo; Humphrey Munene; Charlene A. Wandera; Monda N. Edson; Jane C. Gachura; Tim Hobbs; Festus Ihwagi; Stephen R. Ikhamati; Samson K. Ikiara; David Kimathi; et al. (Land Use Policy, 2024)

Revival of cryopreserved larvae from the important aquaculture species Pacific White Shrimp (Litopenaeus vannamei) using vitrification and ultra-rapid laser warming - Kieran T. Smith; Kanav Khosla; Guebum Han; Tim Humphrey; Nicholas Phelps; John Bischof (Cryobiology, 2024)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Vegetation feedbacks of nutrient addition lead to a weaker carbon sink in an ombrotrophic bog - Tuula Larmola; Jill L. Bubier; Christine Kobyljanec; Nathan Basiliko; Sari Juutinen; Elyn Humphreys; Michael Preston; Tim R. Moore (Global Change Biology, 2013)
To study vegetation feedbacks of nutrient addition on carbon sequestration capacity, we investigated vegetation and ecosystem CO 2 exchange at Mer Bleue Bog, Canada in plots that had been fertilized with nitrogen (N) or with N plus phosphorus (P) and potassium (K) for 7–12 years. Gross photosynthesis, ecosystem respiration, and net CO 2 exchange were measured weekly during May–September 2011 using climate‐controlled chambers. A substrate‐induced respiration technique was used to determine the functional ability of the microbial community. The highest N and NPK additions were associated with 40% less net CO 2 uptake than the control. In the NPK additions, a diminished C sink potential was due to a 20–30% increase in ecosystem respiration, while gross photosynthesis rates did not change as greater vascular plant biomass compensated for the decrease in Sphagnum mosses. In the highest N‐only treatment, small reductions in gross photosynthesis and no change in ecosystem respiration led to the reduced C sink. Substrate‐induced microbial respiration was significantly higher in all levels of NPK additions compared with control. The temperature sensitivity of respiration in the plots was lower with increasing cumulative N load, suggesting more labile sources of respired CO 2 . The weaker C sink potential could be explained by changes in nutrient availability, higher woody : foliar ratio, moss loss, and enhanced decomposition. Stronger responses to NPK fertilization than to N‐only fertilization for both shrub biomass production and decomposition suggest that the bog ecosystem is N‐P/K colimited rather than N‐limited. Negative effects of further N‐only deposition were indicated by delayed spring CO 2 uptake. In contrast to forests, increased wood formation and surface litter accumulation in bogs seem to reduce the C sink potential owing to the loss of peat‐forming Sphagnum .

A Multi-Year Record of Methane Flux at the Mer Bleue Bog, Southern Canada - Tim R. Moore; Allison De Young; Jill L. Bubier; Elyn R. Humphreys; Peter M. Lafleur; Nigel T. Roulet (Ecosystems, 2011)

Contemporary carbon balance and late Holocene carbon accumulation in a northern peatland - NIGEL T. ROULET; PETER M. LAFLEUR; PIERRE J. H. RICHARD; TIM R. MOORE; ELYN R. HUMPHREYS; JILL BUBIER (Global Change Biology, 2007)
Northern peatlands contain up to 25% of the world's soil carbon (C) and have an estimated annual exchange of CO 2 ‐C with the atmosphere of 0.1–0.5 Pg yr −1 and of CH 4 ‐C of 10–25 Tg yr −1 . Despite this overall importance to the global C cycle, there have been few, if any, complete multiyear annual C balances for these ecosystems. We report a 6‐year balance computed from continuous net ecosystem CO 2 exchange (NEE), regular instantaneous measurements of methane (CH 4 ) emissions, and export of dissolved organic C (DOC) from a northern ombrotrophic bog. From these observations, we have constructed complete seasonal and annual C balances, examined their seasonal and interannual variability, and compared the mean 6‐year contemporary C exchange with the apparent C accumulation for the last 3000 years obtained from C density and age‐depth profiles from two peat cores. The 6‐year mean NEE‐C and CH 4 ‐C exchange, and net DOC loss are −40.2±40.5 (±1 SD), 3.7±0.5, and 14.9±3.1 g m −2 yr −1 , giving a 6‐year mean balance of −21.5±39.0 g m −2 yr −1 (where positive exchange is a loss of C from the ecosystem). NEE had the largest magnitude and variability of the components of the C balance, but DOC and CH 4 had similar proportional variabilities and their inclusion is essential to resolve the C balance. There are large interseasonal and interannual ranges to the exchanges due to variations in climatic conditions. We estimate from the largest and smallest seasonal exchanges, quasi‐maximum limits of the annual C balance between 50 and −105 g m −2 yr −1 . The net C accumulation rate obtained from the two peatland cores for the interval 400–3000 bp (samples from the anoxic layer only) were 21.9±2.8 and 14.0±37.6 g m −2 yr −1 , which are not significantly different from the 6‐year mean contemporary exchange.

Gross Anatomy and Histology of the Hook and Skin of Forehead Brooding Male Nurseryfish, Kurtus Gulliveri, From Northern Australia - Tim M. Berra; John D. Humphrey (Environmental Biology of Fishes, 2002)

Behavior of a cell line derived from normal human hepatocytes on non-physiological and physiological-type substrates: Evidence for enhancement of secretion of liver-specific proteins by a three-dimensional growth pattern - Matthew Smalley; Kenneth Leiper; David Floyd; Margaret Mobberley; Tim Ryder; Clare Selden; Eve A. Roberts; Humphrey Hodgson (In Vitro Cellular & Developmental Biology - Animal, 1999)